Software for Matching Standard Activity Enzyme Biosensors for Soil Pollution Analysis - Valentina A. Kratasyuk; Elizaveta M. Kolosova; Oleg S. Sutormin; Viktoriya I. Lonshakova-Mukina; Matvey M. Baygin; Nadezhda V. Rimatskaya; Irina E. Sukovataya; Alexander A. Shpedt (Sensors, 2021)
This work is dedicated to developing enzyme biosensor software to solve problems regarding soil pollution analysis. An algorithm and specialised software have been developed which stores, analyses and visualises data using JavaScript programming language. The developed software is based on matching data of 51 non-commercial standard soil samples and their inhibitory effects on three enzyme systems of varying complexity. This approach is able to identify the influence of chemical properties soil samples, without toxic agents, on enzyme biosensors. Such software may find wide use in environmental monitoring.